PEMBINAAN KARAKTER GEMAR MEMBACA MELALUI GERAKAN LITERASI SEKOLAH DI MADRASAH IBTIDAIYAH NEGERI WONOSOBO - -, Ulfah; Suyud, Robingun; Muntaqo, Rifqi (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2024)
This study employed a descriptive qualitative approach conducted at Madrasah Ibtidaiyah Negeri (MIN) Wonosobo. Data were collected through observation, interviews, and documentation. Informants were selected through data reduction, presentation, verification, and within-case analysis. Data credibility was ensured through reference adequacy checks, while dependability and confirmability were achieved via supervisory audits. The findings reveal three key points: (1) The implementation of the School Literacy Movement (GLS) is conducted in stages—habituation, development, and learning—with teachers playing a central role in fostering a reading culture among students; (2) Evaluation of GLS highlights both supportive and inhibiting factors, including library facilities and students' reading abilities, which significantly influence the development of reading habits; (3) Supporting factors include reading materials, reading corners, wall magazines, and reading posters, while obstacles include students’ lack of interest and the absence of dedicated library staff, resulting in suboptimal library use.